(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2023)
The energy crisis and the climate crisis that are happening in the world are caused by the use of fossil energy which is dangerous because it causes an increase in greenhouse gas emissions so that the climate becomes unstable, therefore, it is necessary to realize the change of energy from fossil fuels to renewable energy by converting vehicles into electricity, for that made an electric conversion motorcycle. The resulting performance is expected to be maximized to replace conventional motorbikes. This study uses the independent variable which in this study is current (I). The controllers used are 30A and 45A controllers the dependent The dependent variables in this study were torque (Nm), Daya (P), engine speed (RPM) obtained from the Dynotest test. The control variable in this study was voltage (V) of 2 kW according to PERMENHUB RI No 65 of 2020. The performance test results obtained by the Dynotest on the motorcycle before conversion obtained the performance test results, namely 9.5 Nm torque at 4169 RPM and 5.8 HP Power at 3648 RPM, the motorcycle after being converted to a 30A controller obtained performance test results, namely 16.22 Nm torque at 1714 RPM Power 6.1 HP at 4671 RPM, the motorbike after being converted to a 45A controller obtained the best performance test results, namely torque of 18.61 Nm at 1141 RPM and Power of 6.1 HP at 5094 RPM. This motorcycle modification replaces the propulsion system using a BLDC electric motor, replaces the Daya source using a battery, and slightly changes the frame by adding a bracket as a place for the battery. In conclusion, the modification of this convertible motorbike is quite good in dealing with the energy crisis where the dependence on using fossil fuels such as fuel oil because this electric conversion motorbike is a form of new renewable energy. This conversion motorbike is also a form of support for the government to implement electric vehicles in Indonesia.